New Form of Hypertonic Solution for Nebulization Therapy - Olga I. Simonova; Yulia V. Gorinova (Вопросы современной педиатрии)
Mucolytic, expectorative and antitussive drugs are traditionally used in acute or chronic respiratory episodes affected by acute respiratory infections. Today, preference is given to drugs in a form of solutions for nebulization therapy. The article presents data on the new dosage form of 7% inhalation hypertonic solution in combination with hyaluronic acid used in mucostasis therapy for chronic respiratory diseases. The information on the properties and the favorable effect of hyaluronic acid is provided. We discuss the evidence base of inhalation of the hypertonic solution in combination with hyaluronic acid in cystic fibrosis.